Agility Factors' Analyses Framework in Project-Oriented Organizations through a Sustainability Approach in Large Projects Case Study: Isfahan Municipality. (17th September 2021) - Tahanian, Ahmadreza; Haleh, Hasan; Etebari, Farhad; Vahdani, Behnam
Abstract : In recent years, the project management concept is coupled with sustainable development. In terms of profitability and adapting to environmental changes, generating value for the customer and responding to market needs is a challenging issue. To gain profit and success, a project should adhere to agility factors. With respect to the importance of project execution success, corresponding to the sustainability dimensions and by developing agility parameters, this study provides a framework for clustering and analyzing "large projects" based on agility factors in project-oriented organizations through a sustainability approach and by applying Quality Function Deployment. To this end, critical factors of project success and then agility factors of the project-oriented organizations have been identified. Thereafter, the importance of these two major components has been measured by executive managers in Isfahan Municipality and academic experts. Afterward, the agility factors' weights have been calculated based on extracted sustainability factors' weights, which have been gained according to the project's critical success factors and by applying quality function deployment. By determining the agility factors' clusters in the project-oriented organizations and calculating their importance weights, the first cluster that contains project communication management, organizational culture, and contracts management gains the maximum weight of importance.